Field evaluation of chemical management of root knot nematodein tomato - and B.N. SHUKLA, INDIRA VADHERA, S.P. TIWARI (Indian Phytopathology, 2002)
Nursery treatment and seedling root dip were evaluated for their efficacy for the management of root knot nematode (Meloidogyne incognita) on tomato (cv. Pusa Ruby) under field conditions at the Department of Horticulture Jawaharlal Nehru Krishi Vishwa Vidyalaya Jabalpur, Madhya Pradesh, India. Carbofuran @ 0.6g a.i/m2 in a nursery bed treatment improved seed germination and seedling vigour, significantly reduced the gall index from 5.0 to 3.6, and increased the yield of tomatoes by 36.9%. Seedlingroot dip for 6 h in carbosulfan (25 ST) and triazophos (40 EC) @0.1% increased the yield by 43 and 42%, respectively, and reduced the gall index to 3.5 and 3.8, respectively compared with 5.0 for the control.